(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2024)
Motor vehicle emissions have become a significant air pollution problem, especially in cities with high industrial concentrations like Kryvyi Rih. Despite ongoing air quality monitoring, assessing the direct impact of vehicles is challenging. Vehicle emissions, primarily released in the lower atmosphere, affect areas where human activity is most concentrated. To evaluate the impact of motor vehicles on air pollution, mathematical models are used to estimate pollutant concentrations based on traffic volume, intensity, fuel type, and other factors. In Kryvyi Rih, areas with the highest traffic intensity were identified, and CO and NO₂ dispersion models were developed. The CALRoads View software, using the CALINE4 model, and “EOL Plus,” based on the OND-86 methodology, were applied. A comparison of the results helped determine the suitable applications of each model for analyzing vehicle emissions in large urban areas.